Формування корпоративної ідентичності - Тарасюк, Людмила (Видавництво Львівської політехніки, 2012)
In this article the problem of how broken corporate culture at the organization. Grounded principles of corporate identity – an employee belonging to the organization.
Keywords: корпоративна культура; організаційна культура; корпоративна ідентичність; символи; міфи; герої; церемонії; місія